A new angiocarpous Lactarius species from Thailand - Verbeken, Annemieke; Hampe, Felix; Wissitrassameewong, Komsit; Hyde, Kevin; Eberhardt, Ursula; Nuytinck, Jorinde (Phytotaxa, 2014)
Lactarius bisporus sp. nov. is described from primary tropical forest in Thailand. Morphological characters and DNA sequence data are given. Comparisons with the closely related angiocarpous taxon Lactarius pomiolens are provided.